Functional variants inPXRare associated with colorectal cancer susceptibility in Chinese populations. Issue 6 (December 2015) - Ni, Haizhen; Su, Bofeng; Pan, Lemen; Li, Xueyan; Zhu, Xixia; Chen, Xiangjian
Highlights: We found that PXR rs3814058C>T polymorphism was associated with a higher CRC risk. We found that rs3814058C to T transition gained a new binding of hsa-miR-129-5p. We found an effected of rs3814058C>T on PXR expression level. Abstract: Background: As an important member of the steroid nuclear receptor family, recent research has suggested that PXR may play important roles in the development of multiple cancers. However, no well-designed studies has been conducted to investigate the associations between genetic polymorphisms of PXR and colorectal cancer (CRC) risk in Chinese populations. Materials and methods: We performed a hospital-based case–control analysis to assess two genetic polymorphisms in the 3′-untranslated regions (3′-UTR) via allele-specific MALDI-TOF mass spectrometry assay and evaluated the associations between two polymorphisms and risk of CRC. Results: The PXR rs3814058C>T polymorphism was significantly associated with a higher risk of CRC ( P  < 10–3), and the CT/TT variant genotypes had an increased CRC risk (adjusted odds ratio = 1.54, 95% confidence interval = 1.27–1.83) comparing CC genotype. In stratified analyses, rs3814058CT + TT genotypes was associated with increased risk among alcohol consumers ( P  = 0.002). In vitro experiments indicated that the rs3814058C to rs3814058T transition gained a new binding of the microRNA hsa-miR-129-5p and decreased the PXR expression. Conclusions: Our data suggest that the functional polymorphism rs3814058C>T in 3′-UTR of PXR may be a functional biomarker to predict risk of CRC.